New implications for prion diseases therapy and prophylaxis - Liu, Fangzhou; Lü, Wenqi; Liu, Ling (Frontiers in Molecular Neuroscience, 2024)
Prion diseases are rare, fatal, progressive neurodegenerative disorders that affect both animal and human. Human prion diseases mainly present as Creutzfeldt-Jakob disease (CJD). However, there are no curable therapies, and animal prion diseases may negatively affect the ecosystem and human society. Over the past five decades, scientists are devoting to finding available therapeutic or prophylactic agents for prion diseases. Numerous chemical compounds have been shown to be effective in experimental research on prion diseases, but with the limitations of toxicity, poor efficacy, and low pharmacokinetics. The earliest clinical treatments of CJD were almost carried out with anti-infectious agents that had little amelioration of the course.With the discovery of pathogenic misfolding prion protein (PrPSc) and increasing insights into prion biology, amounts of novel technologies have attempted to eliminate PrPSc. This review presents new perspectives on clinical and experimental prion diseases, including immunotherapy, gene therapy, small-molecule drug, and stem cell therapy. It further explores the prospects and challenge associated with these emerging therapeutic approaches for prion diseases.